Regarding the assessment of Ukraine’s military-economic security in the context of modern military conflicts - Havryliuk, Ivan; Kliat, Yurii; Vodchyts, Oleksandr; Dobrovolskyi, Yuzef; Hetman, Alevtyna; Fomkin, Denys (Social Development and Security, 2025)
Purpose: consists in developing a system of indicators that affect the state of military and economic security of the state in the conditions of modern military conflicts. Method: analysis; synthesis; comparison; formalization and expert assessment; institutional and risk approaches. Practical implications: a proposed system of indicators for assessing the state of military-economic security of Ukraine in the context of modern military conflicts. Future research: further research should be directed at studying models of economic sustainability in conditions of protracted military conflicts, including scenarios of resource mobilization and economic recovery after the end of hostilities. It is important to focus on analyzing the impact of modern technologies on the provision of the defense-industrial complex and optimizing economic processes for the development of the capabilities of our own armed forces. It is also advisable to focus efforts on studying effective models of logistical support for autonomous military formations and the integration of civilian sectors of the economy into defense systems. Paper type: theoretical, practical.